THE EFFECT OF ALOIN ON BLOOD SUGAR LEVELS IN STREPTOZOTOCIN-INDUCED WHITE MALE MICE (MUS MUSCULUS) - Rendri Bayu Hansah; Abdullah, Dessy; Thira Adiahni (Yayasan Nusantara Hasana Berdikari, 2023)
Blood, a lack of insulin secretion, insulin metabolism and both. One herb that works as well as drop in blood glucose levels and repair the metabolism of insulin is an aloin founded in aloe vera. Aims. Knowing the effect of aloin on white male mice (Mus musculus) induced by STZ. Methode. The type of research is experimental with the approach